2015
DOI: 10.1002/cctc.201500801
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a Fe3O4 Core Enhances the Photocatalytic Activity of MIL‐100(Fe) with Tunable Shell Thickness in the Presence of H2O2

Abstract: Metal–organic frameworks (MOFs) are a new class of porous crystallized materials, which have attracted great interest for sustainable energy and environmental remediation. The functionalization of MOF‐based catalysts has been investigated to improve their photocatalytic ability. Here, we present a way of enhancing a magnetic MOF‐based photocatalyst composed of MIL‐100(Fe) and Fe3O4. The photocatalytic performance of the MOFs was significantly enhanced by the simultaneous introduction of a Fe3O4 core and H2O2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(44 citation statements)
references
References 34 publications
2
42
0
Order By: Relevance
“…As reported by Zhao and colleagues, the Fe 3 O 4 @MIL-100(Fe) core-shellm icrospheres are preparedw ith mercaptoacetic acid-functionalized Fe 3 O 4 ,b enzenetricarboxylic acid, and FeCl 3 ethanol solution at 70 8C. [112] In the solar photocatalysis (P), Fenton-like (F), photo-Fenton-like (PF) systems, all Fe 3 O 4 @MIL-100 catalysts, regardless of the thickness of the MOF shell (prepared with 10, 20, and 40 cycles), exhibit more efficient degradation than pure MIL-100 ( Figure 6a)f or MB degradation with H 2 O 2 addition. In addition, the core-shell catalyst can be easily separated by am agnet and reused from aqueous solution as ar esult of the low M r value (Figure 6b).…”
Section: Mof/metalliferous Junction Photocatalystsmentioning
confidence: 99%
“…As reported by Zhao and colleagues, the Fe 3 O 4 @MIL-100(Fe) core-shellm icrospheres are preparedw ith mercaptoacetic acid-functionalized Fe 3 O 4 ,b enzenetricarboxylic acid, and FeCl 3 ethanol solution at 70 8C. [112] In the solar photocatalysis (P), Fenton-like (F), photo-Fenton-like (PF) systems, all Fe 3 O 4 @MIL-100 catalysts, regardless of the thickness of the MOF shell (prepared with 10, 20, and 40 cycles), exhibit more efficient degradation than pure MIL-100 ( Figure 6a)f or MB degradation with H 2 O 2 addition. In addition, the core-shell catalyst can be easily separated by am agnet and reused from aqueous solution as ar esult of the low M r value (Figure 6b).…”
Section: Mof/metalliferous Junction Photocatalystsmentioning
confidence: 99%
“…For example, Jiang et al 15 presented an approach to construct a photocatalytically active MOF as a catalyst for RhB degradation under visible light. Zhao et al 16 reported that core-shell Fe 3 O 4 @MOFs could be used as a visible-light-driven catalyst for the degradation of dye pollutant with H 2 O 2 as an electron acceptor. Jiang et al 17 observed that MIL-53(Fe) could completely decompose RhB in the presence of H 2 O 2 under visible light irradiation.…”
mentioning
confidence: 99%
“…For the two samples, the Fe 2p1/2 and Fe 2p3/2 peaks were observed at 725.43 eV and 711.27 eV, respectively, with the separation (2p1/2−2p3/2) of 14.16 eV highlighting the existence of Fe 3 O 4 in the Fe 3 O 4 @MIL-100(Fe) and the immobilized lipase. Moreover, the satellite XPS peak at about 717.5 eV was also seen for the two samples, which could be originated from the Fe(III) in the MIL-100(Fe) MOF [30]. Furthermore, the curve-fitting O 1s spectra of the immobilized lipase ( Figure 6e) exhibited three XPS peaks at 530.55 eV, 532.08 eV, and 535.36 eV, attributing to Fe-O, C-O/C=O, and O-C=O in the immobilized lipase, respectively [31,32].…”
Section: Characteristics Of the Immobilized Lipasementioning
confidence: 87%
“…To further verify the successful preparation of the magnetic support and the immobilized lipase, the surface chemical states were investigated by XPS techniques, as shown in Figure 6. The comparative survey spectra ( Figure 6a) exhibited various XPS peaks at binding energies of 286.35 eV, 533.02 eV, and 712.01 eV, which could be attributable to C 1s, O 1s, and Fe 2p for both the magnetic support and the immobilized lipase, respectively [25,30]. More importantly, an extra N 1s XPS peak at a binding energy of 400.36 eV, due to the lipase, was clearly observed in Figure 6a for the immobilized lipase, further confirming that the lipase was practically tethered onto the magnetic composite.…”
Section: Characteristics Of the Immobilized Lipasementioning
confidence: 99%